Răspuns :
Rezolvare :
[tex] \frac{x + 1}{2} - \frac{x}{3 + 5} = \frac{1 - x}{6} [/tex]
rezultă
[tex] \frac{x + 1}{2} - \frac{x}{8} = \frac{1 - x}{6} [/tex]
rezultă
[tex]12(x + 1) - 3x = 4(1 - x)[/tex]
rezultă
[tex]12x + 12 - 3x = 4(1 - x)[/tex]
rezultă
[tex]12x + 12 - 3x = 4x - 4x[/tex]
rezultă
[tex]9x + 12 = 4 - 4x[/tex]
rezultă
[tex]9x + 4x = 4 - 12[/tex]
rezultă
[tex]13x = - 8[/tex]
rezultă
[tex]x = - \frac{8}{13} [/tex]
[tex] \frac{x + 1}{2} - \frac{x}{3 + 5} = \frac{1 - x}{6} [/tex]
rezultă
[tex] \frac{x + 1}{2} - \frac{x}{8} = \frac{1 - x}{6} [/tex]
rezultă
[tex]12(x + 1) - 3x = 4(1 - x)[/tex]
rezultă
[tex]12x + 12 - 3x = 4(1 - x)[/tex]
rezultă
[tex]12x + 12 - 3x = 4x - 4x[/tex]
rezultă
[tex]9x + 12 = 4 - 4x[/tex]
rezultă
[tex]9x + 4x = 4 - 12[/tex]
rezultă
[tex]13x = - 8[/tex]
rezultă
[tex]x = - \frac{8}{13} [/tex]
Rezolvare :
\frac{x + 1}{2} - \frac{x}{3 + 5} = \frac{1 - x}{6}2x+1−3+5x=61−x
\frac{x + 1}{2} - \frac{x}{8} = \frac{1 - x}{6}2x+1−8x=61−x
12(x + 1) - 3x = 4(1 - x)12(x+1)−3x=4(1−x)
12x + 12 - 3x = 4(1 - x)12x+12−3x=4(1−x)
12x + 12 - 3x = 4x - 4x12x+12−3x=4x−4x
9x + 12 = 4 - 4x9x+12=4−4x
9x + 4x = 4 - 129x+4x=4−12
13x = - 813x=−8
x = - \frac{8}{13}x=−138
\frac{x + 1}{2} - \frac{x}{3 + 5} = \frac{1 - x}{6}2x+1−3+5x=61−x
\frac{x + 1}{2} - \frac{x}{8} = \frac{1 - x}{6}2x+1−8x=61−x
12(x + 1) - 3x = 4(1 - x)12(x+1)−3x=4(1−x)
12x + 12 - 3x = 4(1 - x)12x+12−3x=4(1−x)
12x + 12 - 3x = 4x - 4x12x+12−3x=4x−4x
9x + 12 = 4 - 4x9x+12=4−4x
9x + 4x = 4 - 129x+4x=4−12
13x = - 813x=−8
x = - \frac{8}{13}x=−138